Teaching Mathematics in English for Elementary Students of Asak Paroki MKK - Clara Herlina (Social Economics and Ecology International Journal (SEEIJ), 2020)
Mathematics subject is considered difficult for most elementary students, especially when the subject is given in English. To be able to do math exercises in English, the students have to understand the math vocabulary and the concepts of math. The purpose of this community development program is to increase the elementary students’ ability in solving word math problems in English. The participants in this program are twenty elementary students who are included in ASAK Paroki MKK community. The program is created in the form of classroom teaching and activities. In this program, we teach them the basic concepts of math vocabulary, understanding the word problems and the solutions to the problems. We also use several related activities to make the lessons meaningful and comprehensible. The results show that the students are able to solve math problems in English correctly and confidently.